Biomass production of different annual cereal-legume intercrops under Moroccan conditions - Kallida J.R.; Shaimi N.; Loubani N. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
Annual cereal-legume forage mixtures are increasingly used in forage production in Morocco. Four forage cereals oat (cv Ghali), barley (cv Tamellalt), triticale (cv Juanillo) and rye (cv Petkus) were evaluated in mixture with three fodder legumes, fodder pea (cv Naima), Vicia sativa (cv Nawal) and Vicia villosa (cv Ghazza). Two years study was carried out at El Koudia location (N 34°03’, O 6°46’) to investigate the forage yield and growth rates of legumes-cereals mixtures at seeding ratio 75:25 for legume and cereal, respectively. Results showed significant differences among cereals-legumes intercrops for forage dry matter. The average yields were 8.7 and 6.6 t ha-1 respectively for first year and second year. Intercrops of oat-legumes and triticale-legumes provided higher and more stable yields for two years. Rye-legumes intercrops produced intermediate yields, while production of barley-legumes mixtures was lower for both seasons. Best yields were achieved for oat and triticale mixtures with pea in the first year and of both pea and Vicia sativa during the second year. According to the results, yields of cereals intercropped with Vicia villosa, were lower than yields of cereals intercropped with Vicia sativa or pea, except for barley during the first year. The proportions of pea and Vicia sativa in harvested yields were significantly higher than those of Vicia villosa for all the tested mixtures, indicating that pea and secondly Vicia sativa were more competitive when intercropped with any of the tested cereals.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)